We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
138
1
avatar+381 

enter the answers as order pairs

(__,__) or (__,__)

 Apr 10, 2019
 #1
avatar+19326 
+3

-x^2+3x+8 = 2x+2    rearrange

0 = x^2 -x-6     factor

(x-3)(x+2) = 0    means x = 3 and -2

Sub into one of the equations to find the y values    x = 3  y = 8        x = -2  y= -2     (using equation  y = 2x+2)

 Apr 10, 2019

12 Online Users